School shootings and the Never Again Movement - Hillstrom, Laurie Collier (21st-century turning points, 2019)
This volume provides a concise but authoritative overview of the Never Again Movement, which arose in the aftermath of a mass shooting that killed 17 people at a high school in Parkland, Florida, in February 2018. -- From product description